Advances in Corrosion of High-Temperature Materials: Interfacial Migration and Alloy Design Strategies - Aditya Narayan Singh; Shashwat Kumar Swain; Abhishek Meena; Mobinul Islam; Kyung-Wan Nam (Ceramics)
High-temperature structural materials face severe degradation challenges due to oxidation and corrosion, leading to reduced long-term stability and performance. This review comprehensively examines the interfacial migration mechanisms of reactive elements (REs) such as Ti, Al, and Cr in Ni/Fe-based alloys, emphasizing their role in forming and stabilizing protective oxide layers. We discuss how these oxide layers impede ion migration and mitigate environmental degradation. Key findings highlight the importance of selective oxidation, oxide layer healing, and the integration of novel alloying elements to enhance resistance under ultra-supercritical conditions. Advanced insights into grain boundary engineering, alloy design strategies, and quantum approaches to understanding charge transport at passive interfaces are also presented. These findings provide a foundation for developing next-generation high-temperature alloys with improved degradation resistance tailored to withstand extreme environmental conditions.